Strategic hedging in Indonesia's defense diplomacy. Issue 4 (1st October 2016) - Gindarsah, Iis
ABSTRACT: With the rapid pace of regional arms modernization and unresolved territorial disputes, Indonesia is increasingly susceptible to the impact of emerging great power rivalry in Asia-Pacific. Rather than pursuing a robust military build-up, Indonesian policy-makers assert that diplomacy is the country's first line of defense. This article argues that defense diplomacy serves two agenda of Indonesia's hedging strategy – strategic engagement and military modernization. This way, Indonesian defense and security officials seek to moderate the impact of geopolitical changes while maintaining the country's defensive ability against regional uncertainties.